Structural identification of vasodilator binding sites on the SUR2 subunit - Dian Ding; Jing-Xiang Wu; Xinli Duan; Songling Ma; Lipeng Lai; Lei Chen (Nature Communications, 2022)
SUR2-containing KATP channels are drug targets for certain vasodilators. Here, the authors determine high-resolution cryo-EM structures of SUR2 in complex with two vasodilators, P1075 and levcromakalim, uncovering the mechanisms of these drugs.